Effect of Aftershocks on Seismic Fragilities of Single-Story Masonry Structures - Zhang, Hao; Sun, Tong; Hou, Shi-Wei; Gao, Qing-Meng; Li, Xi (Frontiers in Physics, 2021)
The effect of aftershocks on the fragility of single-story masonry structures is investigated using probabilistic seismic demand analysis (PSDA). Finite element models of an unreinforced masonry (URM) structure and a confined masonry (CM) structure are established and their seismic response characteristics when subjected to mainshock, aftershock, and the mainshock–aftershock sequence are then comparatively investigated. The effects of aftershocks and the use of confining members on the seismic response are studied. Probabilistic seismic demand models (PSDM) of the structures are built, and fragility curves under various conditions are derived to investigate the effect of aftershocks on structural fragility. The maximum roof displacement and maximum inter-story drift ratio are lower in the CM model than in the URM model; additionally, the probability of exceedance (PE) values of each damage limit state are reduced, and those of the mainshock-damaged models subjected to aftershock significantly increase compared to those directly subjected to a same-intensity aftershock. The probability of severe damage or collapse com-pared with the mainshock-damaged CM model is greater than when each is subjected to a same-intensity aftershock. The use of confining members benefits aftershock resistance and reduces the failure probability of the mainshock-damaged structure. The PE values significantly increase with the after-shock scaling factor δ. Therefore, the effect of aftershocks should be considered in the seismic design and analysis of masonry structures.